Calculating the gross regional product of the Kurdistan Region-Iraq - Abramzon, Shmuel (Research report (Rand Corporation), 2016)
To lay the foundation for successful policymaking, the Kurdistan Regional Government is seeking to develop comprehensive and reliable statistics on the Kurdistan Region-Iraq (KRI) as it charts a course toward peace and prosperity. In this report, the authors describe efforts to continue building capacity at the Kurdistan Regional Statistics Office (KRSO) by setting up a system for data collection and analysis to support the annual calculation of the gross regional product (GRP), a critical indicator for successful policy planning in many areas. The report presents estimates of the value added by different sectors of the KR' economy for the year 2012 (excluding natural resources, due to lack of available data). The report covers three governorates: Erbil, Sulaymaniyah, and Duhok.